2020
DOI: 10.3390/ijms21103594
|View full text |Cite
|
Sign up to set email alerts
|

Robust Sampling of Defective Pathways in Alzheimer’s Disease. Implications in Drug Repositioning

Abstract: We present the analysis of the defective genetic pathways of the Late-Onset Alzheimer’s Disease (LOAD) compared to the Mild Cognitive Impairment (MCI) and Healthy Controls (HC) using different sampling methodologies. These algorithms sample the uncertainty space that is intrinsic to any kind of highly underdetermined phenotype prediction problem, by looking for the minimum-scale signatures (header genes) corresponding to different random holdouts. The biological pathways can be identified performing posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Considering this, the alterations we observed in the viral and non-viral RNA processing pathways of OM cells can be expected. Similar to our study, pathways related to viral RNA processing have been recently shown to be significantly altered also in RNA samples derived from peripheral blood of patients with LOAD [ 64 ].…”
Section: Discussionsupporting
confidence: 86%
“…Considering this, the alterations we observed in the viral and non-viral RNA processing pathways of OM cells can be expected. Similar to our study, pathways related to viral RNA processing have been recently shown to be significantly altered also in RNA samples derived from peripheral blood of patients with LOAD [ 64 ].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, it seems that sAPPα-APP interactions induce the PI3K/Akt pathway via Gαo activation, and that APP works like GPCR and sAPPα works like its agonist ( Figure 4 ) [ 47 ]. GNG10 is differentially expressed in the hippocampus of AD [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that emetine may have the potential to clear amyloid-beta plaques in AD ( Ahmad et al, 2019 ). The isoquinoline alkaloids emetine and its desmethyl analog cepaheline have been predicted to be protective against cognitive decline and AD ( Fernández-Martínez et al, 2020 ). Withaferin A is a steroidal lactone and a withanolide found in the medicinal plant Withania somnifera, and a number of studies have shown that it plays a neuroprotective role in AD ( Das et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%